Determination of potential sources of Quercus airborne pollen in Córdoba city (southern Spain) using back-trajectory analysis - Hernández-Ceballos, M. a.; García-Mozo, H.; Adame, J. a.; Domínguez-Vilches, E.; Bolívar, J. P.; De la Morena, B. a.; Pérez-Badía, R.; Galan, C.; la Morena, B a.; Pérez-Badía, R.; Galan, C. (Aerobiologia, 2011)
The northern area of Co´rdoba province (southern Spain) is characterised by a high spatial distribution of Quercus species. In Co´rdoba city, high airborne Quercus pollen counts are detected during spring despite the low presence of Quercus populations in the Guadalquivir Valley, where this city is located. This study sought to clarify and identify the potential origin of the different Quercus peaks detected in this city and chart the possible relationship between Quercus pollen curves and air-mass movements. For this purpose, an integrated study of daily and intra-diurnal Quercus pollen counts and back-trajectory analysis was performed over the March–June period of the years 2006–2008. The application of cluster techniques to back trajectory enabled the identiﬁcation of six different types of air-mass movement. As a function of frequency, two different air-mass groups were identi- ﬁed: the main group comprised Local, Slower Northwest and Mediterranean movements, characterised by higher frequencies; a second group consisting of North, Faster Northwest and Southwest trajectories occurred less frequently over the study period. Although a signiﬁcant correlation was observed between Quercus airborne pollen counts recorded in Co´rdoba city and the inﬂuence of the Mediterranean air-mass movements, the strongest positive correlation was found between North and Northwest air-mass movements and daily Quercus pollen counts. These results would conﬁrm both that the major Quercus pollen sources are located at different distances north of the city and a new pollen source is also located south of the province, beyond the Guadalquivir valley, related to the arrival of Mediterranean air masses. The northern source appears to be linked to regional transport and the southern source to long-range transport.
Keywords: HYSPLIT; Mediterranean; Oak pollen; Synoptic conditions; Transport

Airborne pollen records and status of the anemophilous flora in arid areas of the Iberian Peninsula - Carinanos, P.; Galan, C.; Alcazar, R.; Dominguez, E. (JOURNAL OF ARID ENVIRONMENTS, 2010)
This paper reports on the relationship between the airborne pollen spectrum and the status of anemophilous flora in the south-eastern Iberian Peninsula. Variations in pollen counts with respect to data for a previous sampling period were also examined. The key finding was that the spectrum contained pollen from the most characteristic local species, such as xerophytes adapted to arid conditions, ruderal and nitrophilous species, sclerophyllous Mediterranean pine and holm-oak forest and vegetation in dry watercourses. The main variations with respect to earlier data were attributable to changes in land use, with increasing production of certain crops and a growing trend towards ecological agriculture, the introduction of allochthonous species and the recovery of local flora in dry watercourses. (C) 2010 Elsevier Ltd. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 24-28 OVAL RD, LONDON NW1 7DX, ENGLAND publisher: ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD
Keywords: Aerobiology; Airborne pollen records; Arid areas; Phytogeography; Pollen spectrum

Phenological trends in southern Spain: A response to climate change - García-Mozo, H.; Mestre, a; Galan, C. (Agricultural and Forest Meteorology, 2010)
The impact of climate change, and particularly of climate warming, is being tracked in many physical and biological systems. Plant phenology is seen as one of the most important bio-indicators, since trends can provide considerable temporal and spatial information regarding ongoing changes. Analyses performed at six sites in southern Spain from 1986 to the present have focused on vegetative and overall reproductive phenology in Olea europaea L., and Vitis vinifera L. and in various species of Quercus spp. and Poaceae. Early results suggest that trends in ﬂowering patterns derived from ﬁeld phenological observations were similar to trends in aerobiological data for most study species, and indicate a trend towards earlier foliation, ﬂowering and fruit ripening. This advance is more evident in arboreal than in herbaceous species. Statistical analysis showed temperature increase was the major factor affecting earlier foliation, ﬂowering and fruit ripening, as well as prompting delayed leaf fall. Herbaceous species were more affected than trees by changes in rainfall records
Keywords: Aerobiology; climate change; Phenology; pollen

Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain - García-Mozo, H.; Chuine, I.; Aira, M. J. J.; Belmonte, J.; Bermejo, D.; Díaz de la Guardia, C.; Elvira, B.; Gutiérrez, M.; Rodríguez-Rajo, J.; Ruiz, L.; Trigo, M. M. M.; Tormo, R.; et al. (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).
Keywords: Aerobiology; Modelling; oak forest; Phenology; pollen; Quercus

Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain - García-Mozo, H.; Chuine, I.; Aira, M.J. J; Belmonte, J.; Bermejo, D.; Díaz de la Guardia, C.; Elvira, B.; Gutiérrez, M.; Rodríguez-Rajo, J.; Ruiz, L.; Trigo, M.M. M; Tormo, R.; et al. (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).
Keywords: Aerobiology; Modelling; oak forest; Phenology; pollen; Quercus

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M.T. T; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M. T. T.; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Modelling start of oak pollen season in different climatic zones in Spain - García-Mozo, H.; Galan, C.; Aira, M. J. (Agricultural and Forest Meteorology, 2002)
Quercus pollen and meteorological data for several years from eight sites in Spain have been statistically analysed to select the threshold temperature and calculate the mean heat accumulation for predicting the Quercus pollination start in different climatic areas. The growing degree days method, which assumes the daily temperature varies as a sine wave, was used for heat accumulation calculations. Threshold temperatures between 4 and 12 ◦ C were chosen using linear regression equations forced through the origin and their root mean square error (RMSE) of predicted against the observed dates for each observation site. Above the threshold, the average growing degree days (up to 1999) for the studied years was taken as the predictor value. Results showed a relationship between the selected threshold and elevation and a stronger and statistically signiﬁcant correlation between threshold and yearly mean temperature, for each site. Regression analysis indicated that the selected threshold and the calculated heat accumulation were optimum for most of the localities. The validity of the results was tested using the meteorological data for the year 2000 as independent variable and this conﬁrmed that there were only a few days difference between the predicted and observed day of the ﬁrst pollen release for most of the studied localities
Keywords: Aerobiology; oak forest; Phenology; pollen; threshold temperature